A moderate-intensity exercise program, fulfilling the ACSM net energy expenditure recommendations, improves health outcomes in premenopausal women. - Borresen, Erica; Wallenta, Jeanna; Zahler, Kyle; Boyd, Eugene (My University, 2007)
The purpose of this study was to quantify the health outcomes associated with a moderate-intensity 10-week exercise program designed to achieve the American College of Sports Medicine (ACSM) net caloric expenditure guideline of 1000 kcal/wk on a group of apparently healthy, but sedentary premenopausal women.
Color poster with text describing research conducted by Erica Borresen, Jeanna Wallenta, Kyle Zahler, and Eugene Boyd, advised by Lance Dalleck.
Keywords: Exercise for women--Evaluation.; Exercise for women--Health aspects.; Middle-aged women--Health and hygiene.; American College of Sports Medicine--Standards.; Posters.